2023
DOI: 10.1136/bmjopen-2022-068121
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of heart auscultation for detecting valve disease: a systematic review

Abstract: ObjectiveThe objective of this study was to determine the diagnostic accuracy in detecting valvular heart disease (VHD) by heart auscultation, performed by medical doctors.Design/methodsA systematic literature search for diagnostic studies comparing heart auscultation to echocardiography or angiography, to evaluate VHD in adults, was performed in MEDLINE (1947–November 2021) and EMBASE (1947–November 2021). Two reviewers screened all references by title and abstract, to select studies to be included. Disagreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Microsoft Swin Transformer models were modified to analyze cardiac ultrasound video containing left ventricular motion in the following steps: [1] echo frames were pre-processed into a fixed length sequence to be used as training data. [2] a hierarchy of Swin transformers were implemented to a single Transformers Encoders (TE) module to extract spatio-temporal features from the input video frames. [3] The transformers use the shifted window attention technique (Figure 2) to capture both local and global context.…”
Section: Cardiac Ejection Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsoft Swin Transformer models were modified to analyze cardiac ultrasound video containing left ventricular motion in the following steps: [1] echo frames were pre-processed into a fixed length sequence to be used as training data. [2] a hierarchy of Swin transformers were implemented to a single Transformers Encoders (TE) module to extract spatio-temporal features from the input video frames. [3] The transformers use the shifted window attention technique (Figure 2) to capture both local and global context.…”
Section: Cardiac Ejection Fractionmentioning
confidence: 99%
“…Multiple studies have shown diagnostic accuracy for auscultation among doctors have eroded significantly (27-68% accuracy). 2 Point of Care Ultrasound devices can record 2-D Echo images and are often a first line tool to assess cardiac anatomy and function, including wall motion, valve disease and enlargement of heart chambers. A routine echocardiogram takes approximately 10-30 videos and 2000 images, and physicians have extremely limited time to interpret the data.…”
Section: Introductionmentioning
confidence: 99%
“…Aortic stenosis (AS) is the most common valvular heart disease in developed countries, affecting 1 in 50 adults over age 65 and portending significant morbidity and mortality. 1 The majority of patients with AS are asymptomatic, and detection of AS by auscultation has been shown in recent meta-analysis to be highly variable 2 , hence adjunctive methods are needed. Recently, machine learning has identified an association between right-sided precordial U waves (RSPUW) on electrocardiograms (ECG) and moderate to severe aortic stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has increasingly highlighted the efficacy of artificial intelligence (AI) in diagnostic processes utilizing simple testing methods [ 5 , 6 , 7 ]. Nevertheless, these studies typically focus on singular modalities.…”
Section: Introductionmentioning
confidence: 99%